A New MATLAB GUI Tool for Instructing Operation of Power Electronic Rectifiers - Modabbernia, Mohammad Reza; Fakhrmoosavi, Seyed Yaser; Akoushideh, Alireza; Shal, Alireza Ahadpour (EMITTER International Journal of Engineering Technology, 2019)
This study seeks to present an interactive tool, which exploits the GUI related abilities in MATLAB, to investigate power electronic rectifiers operation. The present paper aims to show a flexible and extendable environment for steady state simulation of ideal controlled, uncontrolled, single-phase and three-phase power electronic rectifiers. This is accomplished at the presence of R, L and E loads with or without a flywheel diode. The easy application of our tool makes it feasible to be used by the teacher in the classroom. Also its short running time and the PSpice output netlist make it a remarkable alternative to the MATLAB PowerSim toolbox and PSIM software for studying ac-dc converters. Furthermore, in this paper some basic equations were introduced to analyze single and three-phase rectifiers. Because these equations are common between ac-dc converters, analyzing the different types of rectifiers will be easy for the students. The penultimate issue refers that, the proposed program can cause a variety of single and three phase controlled rectifiers accompanied by various combinations of R, L and E loads to be simulated. Ultimately, obtained results are compared to another well-known simulator’s such as PSpice to verify their accuracy.